Thrixspermum muscaeflorum Rao & Joseph Var. Nilagiricum Joseph & Vajravelu-Orchidaceae-a new variety from Nilgiri Hills South India - Joseph, J.; Vajravelu, E. (Indian Forester, 1981)
A new variety of an orchid Thrixspermum muscaiflorum A.S. Rao et J. Joseph var. nilgiricum Joseph et Vajravelu from Nilgiris hills, South India is described with analytical sketches.